(untitled) (Studia theodisca, 2024)
Rose Ausländer’s poetry is a plea for rights that are universal, but which depend on a careful use of language and thoughtful, reasoned views. She exemplifies this with her clear, experience-laden work. Such language and the dialogues it allows contrast with the superficial and often ignorant discussions in social networks. Derrida’s concept of a «minimum friendship» with oneself and others is necessary to foster true discourse. Ausländer’s poem Gestern illustrates this by criticizing the limitations of identification through official documents like passports and affirming the principle of non-privilege. The gesture of throwing away the passport symbolizes the rejection of hierarchies and opens the space for true humanity and discursiveness, unbound by fixed categories.